To commit or not to commit: Endogenous timing in experimental duopoly markets - Steffen Huck; Wieland Müller; Hans-Theo Normann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
In this paper, we experimentally investigate the extended game with action commitment of Hamilton and Slutsky (1990). In their duopoly game, firms can choose their quantities in one of two periods before the market clears. If a firm commits to a quantity in period 1 it does not know whether the other firm also commits early. By waiting until period 2, a firm can observe the other firm's period 1 action. Hamilton and Slutsky predict the emergence of endogenous Stackelberg leadership. Our data, however, does not confirm the theory. While Stackelberg equilibria are extremely rare we often observe endogenous Cournot outcomes and sometimes collusive play. This is partly driven by the fact that endogenous Stackelberg followers learn to behave in a reciprocal fashion over time, i.e., they learn to reward cooperation and to punish exploitation.
urn:nbn:de:kobv:11-10046254
Keywords: 330